Diversity of mosses in Mt. Makiling forest reserve, Philippines - AILENE A ALCALA (Society for Indonesian Biodiversity, 2019)
Abstract. Alcala AA. 2019. Diversity of mosses in Mt. Makiling forest reserve, Philippines. Biodiversitas 20: 1729-1734. One of the essential parts of ecosystem diversity are the mosses. The study aimed to compare the diversity of mosses along altitudinal gradients in the Makiling and Sipit trails of the Mt. Makiling Forest Reserve (MMFR). Sampling plots were established every 100 m. asl elevation. Moss specimens were collected inside a 100m2 plot and re-examined under dissecting and compound microscope. A total of 77 moss species were identified in all plots established in which 43 and 48 species from Makiling and Sipit trail, respectively. Low species richness in lower elevation can be explained by higher degree of disturbances compared in higher elevation. Furthermore, species richness, diversity and abundance increase with increasing elevation. In contrast, higher temperature decreases species richness, abundance and diversity. In general, moss diversity is positively affected by increasing elevation in both trails. This is also supported by correlation analysis on moss species composition for the two sampling sites while sudden decreases in diversity in sampling plots located at 600 m. asl and 900 m. asl (Sipit Trail) and 800 m. asl and 1,000 m. asl (Makiling Trail) could simply be due to the presence of canopy gaps or disturbances in the site. Results implied that mosses used as indicators for impacts of climate change due to their sensitivity to environmental changes.